Ubiquitin-Dependent and Independent Proteasomal Degradation in Host-Pathogen Interactions - Wojciech Bialek; James F. Collawn; Rafal Bartoszewski (Molecules, 2023)
Ubiquitin, a small protein, is well known for tagging target proteins through a cascade of enzymatic reactions that lead to protein degradation. The ubiquitin tag, apart from its signaling role, is paramount in destabilizing the modified protein. Here, we explore the complex role of ubiquitin-mediated protein destabilization in the intricate proteolysis process by the 26S proteasome. In addition, the significance of the so-called ubiquitin-independent pathway and the role of the 20S proteasome are considered. Next, we discuss the ubiquitin–proteasome system’s interplay with pathogenic microorganisms and how the microorganisms manipulate this system to establish infection by a range of elaborate pathways to evade or counteract host responses. Finally, we focus on the mechanisms that rely either on (i) hijacking the host and on delivering pathogenic E3 ligases and deubiquitinases that promote the degradation of host proteins, or (ii) counteracting host responses through the stabilization of pathogenic effector proteins.